A novel Arabidopsis miRNA, ath-miR38-3P, is involved in response to Sclerotinia sclerotiorum infection - Xu ZHAO; Ya-nan SHAN; Yan ZHAO; Ai-rong WANG; Zong-hua WANG (Journal of Integrative Agriculture, 2016)
Plant defense responses against penetration or colonization of pathogens are mediated by activation and repression of a large array of genes. Host endogenous small RNAs are essential in gene expression reprogramming process. We identified a new Arabidopsis microRNA (miRNA) ath-miR38-3P by high-throughput sequencing and further confirmed it by Northern blot assay. Interestingly, ath-miR38-3P was highly induced after infection of the pathogen Sclerotinia sclerotiorum. Further analysis based on the miRNA target database demonstrated that ath-miR38-3P might target to five putative genes: AT2G03140, AT5G59430, AT5G66320, AT1G36620 and AT3G03820. To confirm the target, we conducted the quantitative real-time PCR to observe the expression pattern of each candidate gene. The results showed that only AT3G03820 was down-regulated after inoculation of S. sclerotiorum. In addition, overexpression of ath-miR38-3P down-regulates AT3G03820, suggesting AT3G03820 might represent the target for ath-miR38-3P Our results may provide the useful information for further studying the biological function of a novel ath-miR38-3P and its targets in Arabidopsis-Sclerotinia interaction.